Computational Simulation Studies on the Binding Selectivity of 1-(1H-Benzimidazol-5-yl)-5-aminopyrazoles in Complexes with FGFR1 and FGFR4 - You-Lu Pan (Molecules, 2018)
Fibroblast growth factor receptor 1 (FGFR1) has become a potential target for the treatment of cancer. Designing FGFR1-selective inhibitors remains fundamental to the development of anti-cancer drugs because of highly sequential homology among FGFR subtypes. In present work, four inhibitors were examined with intermolecular interaction patterns with FGFR1 and FGFR4, respectively, for the exploration of binding mechanisms by applying a combined approach of computational techniques, including flexible docking, binding site analyses, electronic structure computations, molecular dynamic simulations, and binding free energy predictions. Molecular simulation-predicted binding conformations and pharmacophoric features of these molecules in the active pocket of either FGFR1 or FGFR4. MMPB(GB)SA-calculated binding free energies were accordant with the ordering of their tested potency values. Furthermore, in silico mutations of two residues (FGFR1: Tyr563 and Ser565) were also performed to check their impact on ligand binding by applying MD simulations and binding free energy calculations. The present studies may provide a structural understanding of the FGFR1-selective mechanism. The viewpoints from computational simulations would be valuable guidelines for the development of novel FGFR1-selective inhibitors.